IMPROVING GRADE VIII STUDENTS™ ACHIEVEMENT IN READING DESCRIPTIVE TEXT THROUGH RECIPROCAL TEACING - Alam, Yovi Tri Asni; Ginting, Siti Aisah (TRANSFORM: Journal of English Language Teaching and Learning, 2014)
ABSTRACT This research attempts to improve students™ achievement in reading descriptive text through reciprocal teaching. The instruments for collecting data were multiple choice test as the quantitative data and diary notes, questionnaire sheet, and observation sheet as the qualitative data. In the orientation test the mean scores was 49.17, in the first competence test the mean score was 63.29, and in the second competence test the mean score was 83.69. The improvement also can be seen from the percentage of students™ reading comprehension; in the orientation test 0% (0 students) got 75 points. In the first competence test 21.62% (eight students) got 75 points. It means there was an improvement about 21.62%. In the second competence test 78.37% (twenty nine students) got 75 points. The improvement was 56.75 %. It can be concluded that Reciprocal Teaching could improve students™ reading descriptive text.   Keywords: Achievement, Reading, Descriptive Text, Reciprocal Teaching